2014
DOI: 10.1093/infdis/jiu633
|View full text |Cite
|
Sign up to set email alerts
|

Differences in HIV Type 1 Neutralization Breadth in 2 Geographically Distinct Cohorts in Africa

Abstract: To investigate whether distinct populations have differing human immunodeficiency virus type 1 (HIV) neutralizing antibody responses, we compared 20 women from Tanzania's HIV Superinfection Study (HISIS) cohort, who were infected multiple HIV subtypes, and 22 women from the Centre for the AIDS Programme of Research in South Africa (CAPRISA) cohort, who were infected exclusively with HIV subtype C. By 2 years after infection, 35% of HISIS subjects developed neutralization breadth, compared with 9% of CAPRISA su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Indeed, in the parent IAVI cohort study, heterologous neutralization was detected in less than 2% of individuals at 24 months post-infection [36]. The ability to neutralize heterologous Env variants that the immune response has not encountered, loosely defined as neutralization breadth, has been shown to develop in plasma by around 2–4 years after HIV-1 infection, in anywhere from 10 to 80% of individuals, depending on the nature of the cohort, timing of sample collection, and the methods used to evaluate and quantify breadth [18,21,22,33,34,36,41,49,50]. In agreement with these findings, neutralization scores indicative of breadth in the IAVI study were generally first observed at a mean of 3.5 years [36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in the parent IAVI cohort study, heterologous neutralization was detected in less than 2% of individuals at 24 months post-infection [36]. The ability to neutralize heterologous Env variants that the immune response has not encountered, loosely defined as neutralization breadth, has been shown to develop in plasma by around 2–4 years after HIV-1 infection, in anywhere from 10 to 80% of individuals, depending on the nature of the cohort, timing of sample collection, and the methods used to evaluate and quantify breadth [18,21,22,33,34,36,41,49,50]. In agreement with these findings, neutralization scores indicative of breadth in the IAVI study were generally first observed at a mean of 3.5 years [36].…”
Section: Resultsmentioning
confidence: 99%
“…Features of HIV-1 Env have been previously associated with the level and type of neutralization breadth that develops within an individual [9,33,38]. Indeed, in the IAVI study involving multiple HIV-1 suptypes, subtype C infection was a significant correlate of higher neutralization breadth score [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated a positive correlation between plasma viral load and titers of neutralizing antibodies to heterologous virus proposing that the development of these antibodies was a consequence of viral replication [ 9 , 19 , 19 , 22 , 22 ]. Broadly cross-neutralizing activity has also been associated to partial B-cell restoration and it has been shown to be variable over time [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on clinical variables associated with the development of bNAb responses did not show a strong association with the gender of the infected individual [8,11,14,15,53,54,55,56]. A lower frequency of neutralization breadth was, however, detected amongst females in the Swiss 4.5k Screen [15,38].…”
Section: Resultsmentioning
confidence: 83%